Pengembangan Kewirausahaan Bagi Mahasiswa Melalui Program Wirausaha Merdeka Dengan Inovasi Pengolahan Daun Kelor (Moringa Oleifera) Menjadi Teh Keloruma - Hasmarani, Hesti; Arif, Muhammad (Universitas Muhammadiyah Surakarta, 2026)
The high unemployment rate among college graduates increases the importance of developing an entrepreneurial spirit among students. The Independent Entrepreneurship Program, which is part of the Independent Learning Campus (MBKM), provides students with the opportunity to develop business ideas based on local potential. This study aims to analyze the development strategy of the herbal tea business